Driving gender equality in the automotive industry: a review of educational strategies - Zavala-Parrales, Ana; Meléndez-Anzures, Frank E.; Perez-Suarez, Sonia; Dominguez, Angeles (Frontiers in Education, 2025)
The automotive industry has historically been characterized by male dominance, presenting significant challenges to achieving gender equality. Despite ongoing efforts to increase female participation, women continue to encounter systemic barriers, including entrenched gender stereotypes, unequal access to training, and a scarcity of female role models. This study systematically reviews educational strategies to advance women’s inclusion in the automotive sector, focusing on their effectiveness in enhancing skills development, career progression, and leadership opportunities. Through the analysis from various regions and organizational contexts, key findings reveal that targeted interventions—such as vocational training programs, mentoring initiatives, leadership development workshops, and scholarship opportunities—have effectively improved women’s technical competencies, professional confidence, and long-term retention in the industry. Additionally, the study highlights that these educational programs yield broader organizational and societal benefits, including increased workplace diversity, enhanced innovation, and improved productivity. Despite these positive outcomes, the research identifies persistent gaps that require further attention, such as the need for policy-driven frameworks to ensure sustained progress and the significance of cross-sector collaboration to amplify the impact of educational initiatives. This review offers evidence-based insights and practical recommendations for policymakers, industry leaders, and educators to support women’s empowerment in the automotive workforce, underscoring the ongoing efforts necessary to achieve meaningful and sustainable gender equality in the sector.